11.39% efficiency Cu2ZnSn(S, Se)4 solar cells from scrap brass. Issue 2 (2nd February 2022) - Pan, Yining; Yan, Chang; Zhao, Xiangyun; Chen, Wangxian; Sun, Kaiwen; Wu, Qing; Ding, Liming; Liu, Fangyang
Abstract : Kesterite Cu2ZnSn(S, Se)4 is one of the most promising next‐generation thin‐film photovoltaic materials. Along with the efficiency advancement of kesterite solar cells, a cost‐effective fabrication process with low carbon footprint plays an increasingly important role considering the near‐future industrialization of CZTSSe solar cells. In this study, we proposed an environmental friendly process to recover copper and zinc from the scrap brass, which can be directly used as the precursor salts to fabricate efficient CZTSSe thin‐film solar cells. The best power conversion efficiency (PCE) of the device using the proposed eco‐friendly process is 11.39% (certified at the National PV Industry Measurement and Testing Center) for CZTSSe solar cells.